2005
DOI: 10.1007/s00167-005-0664-3
|View full text |Cite
|
Sign up to set email alerts
|

Arthrodesis of the knee after failed infected total knee arthroplasty

Abstract: Infection after total knee arthroplasty (TKA) can be a challenging and difficult problem to treat. In selected patients, knee arthrodesis is a well-recognized salvage procedure after infected TKA. The authors retrospectively reviewed their experience with this treatment option, presenting 20 patients (8 women, 12 men), performed between 1990 and 2002. The average age was 67 years (range: 47-81 years) and the mean number of previous surgical procedures was 6 (range: 4-11 procedures). There were multiple indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 28 publications
3
58
0
9
Order By: Relevance
“…SF-12 measurements in our patients with fusion are comparable to other patients with fusion in the literature [6,34]. Of note, the finding that the MCS scores were lower in patients undergoing AKA compared to patients undergoing fusion is different from the findings in the tumor literature [1,12].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…SF-12 measurements in our patients with fusion are comparable to other patients with fusion in the literature [6,34]. Of note, the finding that the MCS scores were lower in patients undergoing AKA compared to patients undergoing fusion is different from the findings in the tumor literature [1,12].…”
Section: Discussionsupporting
confidence: 53%
“…When chronic antibiotic suppression and reimplantation do not work, knee arthrodesis, AKA, and resection are the only remaining options. Klinger et al [34] reported a series of 20 patients who underwent arthrodesis as a treatment for failed infected TKA and found arthrodesis provided a stable and painless extremity for ambulation after failed infected TKA. On the other hand, older trauma studies demonstrated patients receiving fusions do worse than those receiving amputations, as they have worse limb function, decreased quality of life, and more complications [16,18].…”
Section: Discussionmentioning
confidence: 99%
“…Pain was assessed in all patients with a VAS, which uses a simple numerical score of 0 to 10 [18]. The assessment of health-related quality of life after the procedure was measured used the SF-12 Health Survey version 2 (SF12v2) [31].…”
Section: Followup Outpatient Protocolmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Ek lem don du rul ma sı, in ternal ve eks ter nal fik sas yon yön tem le ri ile uy gu la nabil mek te dir. İli za rov eks ter nal fik sa tör tek ni ği nin kul la nıl dı ğı ek lem don du rul ma sı uy gu la ma sı nın bir çok avan ta jı bu lun mak ta dır.…”
Section: Total Diz Protezi Sonrası Gelişen Kompleks Açık Yara Tedavisunclassified
“…Plak vi da tes pi ti nin ise ya ra ka pa ma da ki zor luk lar, plak kı rıl ma sı, en fek te vaka lar da uy gu la na ma ma sı gi bi so run la rı mev cuttur. 3,7 Eks ter nal fik sas yon yön tem le ri ara sın da tek ve ya iki düz lem li fik sa tör ler, İli za rov fik sa tö rü sayı la bi lir. İli za rov eks ter nal fik sa tör kul la nı la rak yapı lan ek lem don du rul ma sı nın bir çok avan ta jı var dır.…”
Section: Re Si̇munclassified